Trading N and O. Part 4: Asymmetric synthesis of syn-β-substituted-α-amino acids - Davies, S; Fletcher, A; Greenaway, C; Kennedy, M; Mayer, C; Roberts, P; Thomson, J (Elsevier, 2018)
A total of nine enantiopure syn-β-substituted-α-amino acids have been synthesised, comprising both syn-β-hydroxy-α-amino acids and syn-β-fluoro-α-amino acids. The key step in the synthetic strategy towards these syn-β-substituted-α-amino acids involves a stereospecific rearrangement, which proceeds via the intermediacy of the corresponding aziridinium ions. The requisite enantiopure syn-α-hydroxy-β-amino esters were prepared via asymmetric aminohydroxylation of the corresponding α,β-unsaturated esters followed by epimerisation of the resultant anti-α-hydroxy-β-amino esters at the C(2)-position. Subsequent activation of the α-hydroxy moiety as a leaving group followed by displacement by the β-amino substituent gave the corresponding aziridinium species. Regioselective in situ ring-opening of the aziridinium intermediates with either water or fluoride gave the corresponding syn-β-hydroxy-α-amino ester or syn-β-fluoro-α-amino ester, respectively, and N-deprotection and ester hydrolysis afforded the target syn-β-substituted-α-amino acids as single diastereoisomers in good overall yield.